Performing Methods of the G.Tsendorj’s Prelude and Fuga op. 59 - Altansukh, Enkh-Amgalan; Bayanjargal, Oyunbadrakh (Mongolian Journal of Arts and Culture, 2025)
The fugue, one of the greatest achievements of Western classical polyphony, is recognized as the foundation of academic transcript of polyphony in Mongolia. The first textbook, Strict Counterpoint (Book 1), was published in 1974, followed by Fugue (Book 2) in 1979, both written by Janchiv D. In addition, the first Mongolian compositions in this genre, a cycle of Preludes and Fugues (nos. 1–4, 1976; nos. 1–2, 1986), were created by G. Tsendorj, comprising a total of seven pairs of preludes and fugues. Within Op. 59, Nos. 1 and 2, each composition is structured in close relation to the classical tradition of the prelude and fugue. Their form and construction are analyzed with attention to performance technique, including hand positioning, fingering choices, and methods of overcoming difficulties in conveying musical imagery, with particular focus on effective interpretation and performance practice. Thus, the significance of bringing the composition into circulation and its contribution to professional musical art is revealed. The study was conducted using general research methods such as analysis, synthesis, and observation, and was further clarified through an examination based on performance practices of musical compositions. Г.Цэндоржийн Прелюди ба фуга (дэс.59)-ийг хөгжимдөх арга барил Хураангуй: Өрнийн сонгодог хөгжимд бүрэлдэн бий болсон олон хоолойн хөгжмийн дээд хэлбэр болох фуга нь монголын сонгодог хөгжимд анхлан сурах бичиг хэлбэрээр танигдсан. Үүнийг “Олон хоолойн ухаан” I дэвтэр “Чанд бичлэгийн контрапункт” (1974), “Олон хоолойн ухаан” II дэвтэр “Фуга” (1979) нэртэйгээр Д.Жанчив зохиож олны хүртээл болгожээ. Харин анхны хөгжмийн зохиолыг Г.Цэндорж төгөлдөр хуурт зориулж Прелюди ба фуга дэс.59 №1, 2, 3, 4 (1979), №1, 2, 3 (1986) гэсэн нийт долоон Прелюди ба фугийн хослолыг зохиосон байна. Тус дэс.59 №1, 2 зохиолыг сонгодог уламжлалт Прелюди ба фугатай уялдуулан бүтэц, хэлбэрийг олох, хөгжимдөх гарын тавил, хурууны дугаарын сонголт, хөгжмийн дүрслэлийг илэрхийлэхэд гарах хүндрэлийг даван туулах, хэрхэн хөгжимдөх арга барилыг судалж тодруулахыг зорьсон. Ингэснээр зохиолыг эргэлтэнд оруулах, мэргэжлийн хөгжмийн урлагт ач холбогдолыг нээн илрүүлэх ач холбогдолтой. Судалгаанд задлан шинжлэх, нэгтгэн дүгнэх, ажиглалтын ерөнхий аргуудаас болон хөгжмийн зохиолыг хөгжимдөх арга барилд суурилан судалж тодрууллаа. Түлхүүр үгс: олон хоолой, хөгжмийн зохиол, хөгжимдлөг, боловсруулга, төгөлдөр хуурч